Coombs-positive Paroxysmal Nocturnal Haemoglobinuria. Issue 3 (30th March 2020) - Kalam, Sabrina; Beale, Rupert; Hughes, Derralynn; Kulasekararaj, Austin; Srirangalingam, Umasuthan
Abstract: Autoimmune haemolytic anaemia (AIHA) and paroxysmal nocturnal haemoglobinuria (PNH) are two distinct causes of haemolytic anaemia. They have different mechanisms that underpin their pathogenesis and, therefore, require different treatment strategies. The direct antiglobulin test (DAT) or Coombs test is positive in cases of immune-mediated haemolytic anaemia and, thus, is positive in AIHA but negative in PNH. We report a case of a woman presenting with a haemolytic anaemia who was found to have concomitant evidence of AIHA and PNH. The case highlights the importance of carrying out a comprehensive haemolysis work-up in patients who present with haemolytic anaemia.